Superior vena caval obstruction: a rare presentation of Behcet's disease. Issue 12 (17th December 2020) - Nair, Avinash Anil; Christopher, D J; Moidu, Fazil; Chandran, Divya
Abstract : A 25-year-old Indian man presented with low-grade fever followed by gradually increasing swelling of neck and face. Physical examination showed bilateral neck swelling, facial swelling and dilated veins in the upper chest. Superior vena cava (SVC) obstruction due to an underlying malignancy was suspected. CT thorax showed large saccular aneurysm with thrombosis of bilateral subclavian arteries of which the right one caused external compression of right innominate vein draining into the SVC. A history of recurrent oral and scrotal ulcers was obtained following which skin pathergy test was done, which was suggestive of a diagnosis of Behcet's disease (BD). He responded to treatment with steroids and azathioprine. This report illustrates that rare nonmalignant cause such as BD could also present with SVC obstruction.